Preparation of nano metal sulphides by thermal decomposition of synthesized metal dithiocarbamate complexes - Abdullah, Nurul Hidayah (2015)
Metal sulphides are important semiconductor materials, which are useful in various applications such as solar cells, optical coatings, photoconductors, and transductors. In this study, several metal dithiocarbamates have been synthesized as single source precursors for metal sulphides production. The preparation of metal dithiocarbamate was done from the reaction between N-ethylcyclohexanamine with carbon disulphide and metal salt in alkaline media. Some difficulties related to high reaction temperatures, precursors instability, and difficult synthetic procedures have somewhat limited the synthesis of single precursor to certain metal complexes. These compounds were found to be effective precursors for nanomaterial fabrication by thermal decomposition of metal dithiocarbamates in a tube furnace. Considering the wide scope of the subject, current research is restricted to the dithiocarbamates with eight metals,namely, zinc(II), nickel(II), copper(II), cobalt(II), cadmium(II), indium(III),antimony(III), and bismuth(III). Besides, no surfactant was used in this study due to the toxicity although many researchers preferred to use surfactants to control the sizes and shapes of the final product. All metal complexes were characterized by Fourier transform infrared (FT-IR) spectroscopy, carbon, hydrogen, nitrogen and sulphur (CHNS) analyses, direct injection mass spectrometry (DIMS) analysis, thermal gravimetric and differential thermal gravimetric (TGA/DTG) analyses, differential scanning calorimetry (DSC), inductively coupled plasma (ICP) and single crystal X-ray diffraction (XRD) analysis. The physical and elemental analyses of Zn, Cd, Cu dan Ni dithiocarbamates (DTC) complexes were confirmed to have the molecular formula of C18H32N2S4M (where M is for Zn, Cd, Cu and Ni metal). On the other hand, the molecular formula of C27H48N3S6M was confirmed for Co, Sb, In, and Bi-DTC. The formation of Zn, Ni, Cu and Sb-DTC crystals were analyzed by single crystal X-ray diffraction analysis to determine the detailed molecular geometry and intermolecular interaction. Thermal study indicated the percentages of residues left were close to the theoretical values attributed to the decomposition of the organic species of the complex. The synthesized metal dithiocarbamates were subjected to thermal treatment at different calcination durations for the preparation of nano metal sulphides. The properties of the metal sulphides were characterized by powder X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive Xray (EDX), transmission electron microscopy (TEM) and ultraviolet-visible (UV-Vis) reflectance spectroscopy. From XRD spectra, metal sulphides were obtained after heat treatment of metal dithiocarbamates for 2, 4 and 6 h at temperature 400 °C. No impurities were observed from the spectra indicated the purity of the product. Different calcination durations did not affect the crystalline phase but only cause a slight change in the peak intensities. FESEM and TEM showed some of the metal sulphides were in the form of nanoparticles, nanowhiskers, and nanorods. However some of them were agglomerated. Energy Dispersive X-Ray (EDX) analysis showed the composition of metal sulphides were close to the theoretical values. The direct band gap observed for all metal sulphides except for cadmium sulphide indicated the blue shift if compared to the bulk sample. The band gap energies of the resultant metal sulphides could possess interesting optical properties and might have significance for future nanoscale device applications.